Hubungan Pelaksanaan Handover SBAR dengan Komunikasi Interprofesional Perawat di RSUD Kota Tanjungpinang Tahun 2023 - Sri Muharni; Utari Christya Wardhani; Yusniar Yusniar (Akademi Analis Kesehatan Pekalongan, 2023)
Interprofessional communication is a process in planning, implementing and evaluating communication programs aimed at health service providers. Handover is the process of transferring the main authority and responsibility for providing clinical care to patients from one nurse to another. The implementation of the SBAR Handover and interprofessional communication was not optimal, decreasing from 98% in January-March to 95% in July-August. This research is to determine the relationship between the implementation of the SBAR handover and the interprofessional communication of nurses at the Tanjungpinang City Hospital in 2023. This research is a quantitative research using an analytical survey. The total population was 150 respondents. The sample in this study was 60 respondents. The sampling technique is non-probability sampling with purposive sampling technique. The data analysis used was the Chi-square test with a significance of 0.05. There is a relationship between SBAR handover and interprofessional communication between nurses at Tanjungpinang City Regional Hospital. Implementing good SBAR handovers and good interprofessional communication between nurses has a big influence in optimizing the provision of nursing care and improving the quality of service in hospitals. It is hoped that nurses will further improve solid collaboration when working through the implementation of SBAR handovers and interprofessional communication in accordance with standards.